2017
DOI: 10.18632/oncotarget.17547
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1: a novel prognostic biomarker in head and neck squamous cell carcinoma

Abstract: BackgroundThe PD-1 receptor and its ligands PD-L1 and PD-L2 are known to be significantly involved in T-cell regulation. Recent studies suggest that PD-L1 expression in malignant tumors contributes to an immunosuppressive microenvironment and disruption of antitumoral immune response. Drugs targeting this pathway are already tested in clinical trials against several tumor entities with promising results. However, until now comprehensive data with regard to PD-L1 and PD-L2 expression in head and neck squamous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 35 publications
(43 reference statements)
2
78
0
Order By: Relevance
“…PD‐L1 expression in TCs impairs T‐cell regulation, disrupts the antitumoral immune response, and contributes to an immunosuppressive microenvironment, allowing tumour immune escape . In several cancer types, such as HNSCC, oropharyngeal squamous cell carcinoma (SCC), pulmonary adenocarcinoma, oesophageal SCC, and urothelial carcinoma, PD‐L1 immunoexpression has been reported to be associated with advanced tumour stage, poor clinical outcome, and/or decreased overall survival. Similarly, in a cohort of 219 salivary gland carcinomas of various types, including 31 SDCs, Mukaigawa et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD‐L1 expression in TCs impairs T‐cell regulation, disrupts the antitumoral immune response, and contributes to an immunosuppressive microenvironment, allowing tumour immune escape . In several cancer types, such as HNSCC, oropharyngeal squamous cell carcinoma (SCC), pulmonary adenocarcinoma, oesophageal SCC, and urothelial carcinoma, PD‐L1 immunoexpression has been reported to be associated with advanced tumour stage, poor clinical outcome, and/or decreased overall survival. Similarly, in a cohort of 219 salivary gland carcinomas of various types, including 31 SDCs, Mukaigawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…The normal physiological interaction between PD‐L1 and PD‐1 inhibits the immune response and promotes self‐tolerance . In many human cancers, including head and neck carcinoma, the PD‐1/PD‐L1 pathway is used by TCs to evade recognition by the host immune system …”
Section: Introductionmentioning
confidence: 99%
“…PD-1 and PD-L1 expression currently remain the most significant tissue biomarkers. PD-L1 expression has been associated with postchemotherapy (docetaxel/platinum/5-fluorouracil regimen) status, 127 co-occurrence with p16 INK4 expression, 131 and poorer OS 124,126,128 (but improved RFS 125,129 and OS 125,130 ). Among these studies, associations between high PD-L1 expression and favorable OS were all demonstrated in post-surgery HNSCC patients.…”
Section: Predictive Tissue Markers For Egfrtargeted Therapymentioning
confidence: 99%
“…Because of the cost of these treatments and their toxicity, identifying biological parameters that predict their efficacy in individual patients is required (26,34). Out of the five most important parameters that define the «tumour immunogram» (26), we found that at least three are associated with the SERPINB3 status: i) the presence of an immune infiltrate; ii) high expression of the immune checkpoint modulator PD-L1, a marker associated with a better response to immunotherapy in HNSCC (7,8,35); iii) tumour sensitivity to immune effectors, such as Ifn-γ, as shown here with the IFNG signature reported by Chow et al (27). Interestingly, similarly to our observations with SERPINB3, high expression levels of another tumour marker, Alpha-foetoprotein (AFP), were recently found in hepatocellular carcinoma cells with increased expression of PD-L1 (36).…”
Section: Discussionmentioning
confidence: 99%